A STUDY ON MARKETING STRATEGIES AMONG AGRICULTURAL ENTREPRENEURS WITH SPECIAL REFERENCES TO SALEM DISTRIC - Subha, N.; S.R, Sathiyanarayanan; Thirumoorthi, B.; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
The development of free market economy has inflicted the Small-Scale-Farmer Entrepreneur more likely in a Continual Basis. Absence of supportive policies and access to funds has marked the Agricultural Entrepreneurs with slow growth rate, meager turnovers, technologically suppressed and even closure of business to some extremes. However, in the recent decades, farmers changing role in a free market focused economy has made them becoming of more entrepreneurial and competitive in their farming businesses. In a State like Tamilnadu, Agro- Entrepreneurship is not an old chapter it is of relatively a new occurrence. Therefore, the main aim of this research study is to study the marketing strategy and techniques of agricultural entrepreneurs in Salem District and to discussing the entrepreneurs marketing solutions for Agro-Products and to analyzing the personal profile factors of the agricultural back rounded entrepreneurs and to study problems faced by rural Agricultural based entrepreneurs in Salem district then promote innovation to further strengthening the competitiveness of rural Agrobased Entrepreneurs. Penetrate wider and deeper to the opportunities and challenges of Agricultural Entrepreneurs and their contributions to the State economy. Also, the paper would aim in addressing suggestive and remedial measures and policy implications based on the research findings.